Philosophical Analysis of Space and Time In Ibn Arabi’s Teachings - kizi, Yarashova (Jurnal Studi Ilmu Alquran dan Tafsir, 2025)
This article analyzes the philosophical views on the concepts of time and space as contemplated by Ibn Arabi. The main goal is to examine the essence of time from Ibn Arabi’s sufistical perspective, its role as a means of connection with the Divine, and its relationship with the movement of the universe. The article discusses the interconnection between the concepts of time and space, as well as the link between time and quantity. Ibn Arabi defines the relative and dialectical characteristics of time by explaining its continuity, circular movement, and the movement in existence. Additionally, the value of time in sufism, its inseparable significance in human life, and the necessity of understanding the immeasurable nature of time are highlighted.